A study of TaRL in developing teaching modules in Kurikulum Merdeka - Ice Novita Triana Lolon; Christian Elyesar Randalele; Sul Hastevin (Himpunan Pengembang Kurikulum Indonesia, 2026)
The implementation of the Kurikulum Merdeka requires differentiated learning through the Teaching at the Right Level (TaRL) approach. However, teachers in the regions often face obstacles to adapting due to limited competence in designing independent learning. This study aims to analyze the obstacles faced by Pendidikan Agama Kristen (PAK) teachers in Elementary Schools in North Toraja Regency when developing the Independent Curriculum Teaching Module, and to formulate an instructional design that integrates the TaRL approach into the tool. Using a qualitative approach and purposive sampling, four PAK teachers (coded G1-G4) were selected as informants. Data were collected through in-depth interviews, observations, and document analysis, and then analyzed using the Miles data condensation model. The results of the study indicate substantive pedagogical obstacles: teachers have difficulty developing valid, real-time diagnostic assessment instruments, formulating inclusive trigger questions, compiling graded Lembar Kerja Peserta Didik (LKPD), and determining indicators to increase students' ability levels. Due to the high dependence on the government's instant draft, the practice of flexible grouping in classes often causes chaos in class management and time constraints, leading teachers to return to the conventional classical model. Abstrak Implementasi Kurikulum Merdeka menuntut pembelajaran berdiferensiasi melalui pendekatan Teaching at the Right Level (TaRL), namun sering kali guru di daerah mengalami kendala dalam beradaptasi karena keterbatasan kompetensi dalam merancang pembelajaran secara mandiri. Penelitian ini bertujuan untuk menganalisis kendala yang dihadapi guru Pendidikan Agama Kristen (PAK) di sekolah dasar di Kabupaten Toraja Utara dalam menyusun Modul Ajar Kurikulum Merdeka, serta merumuskan desain instruksional yang mengintegrasikan pendekatan TaRL ke dalam perangkat tersebut. Melalui pendekatan kualitatif dengan teknik purposive sampling, empat guru PAK (kode G1 sampai G4) dipilih sebagai informan. Data dikumpulkan melalui wawancara mendalam, observasi dan analisis dokumen, yang kemudian dianalisis menggunakan model kondensasi data Miles. Hasil penelitian menunjukkan adanya hambatan pedagogis yang substantif: guru kesulitan menyusun instrumen asesmen diagnostik yang valid dan real-time, merumuskan pertanyaan pemantik yang inklusif, menyusun Lembar Kerja Peserta Didik (LKPD) yang bertingkat, serta menentukan indikator kenaikan level kemampuan murid. Akibat ketergantungan yang tinggi pada draf instan pemerintah, praktik pengelompokan berdasarkan tingkat kemampuan (flexible grouping) di kelas sering memicu kekacauan dalam manajemen kelas dan kendala waktu, sehingga guru cenderung kembali ke model klasikal konvensional. Kata Kunci: Kurikulum Merdeka; modul ajar; TaRL